Agreement between the Stages Cycling and PowerTap Powermeter - Schneeweiss, P.; Haerlen, S.; Ahrend, M.-D.; Niess, A. M.; Krauss, I. (Journal of Science and Cycling, 2018)
Several powermeters for almost every type of bicycle are available. The PowerTap (CycleOps) quantifies cycling power and cadence in the rear wheel hub and has already been validated in previous studies. The Stages Cycling Powermeter (Stages Cycling) is lower-priced and more flexible for usage as it measures in the left crank arm. The aim of this study was to determine the agreement between these two devices.